A Critique of the role of the government in combatting human trafficking in Kenya - Odhiambo, Tracy Adhiambo (Strathmore University, 2017)
Human trafficking has been defined as the recruitment, transportation, transfer, harbouring or receipt of persons, by means of the threat or use of force or other forms of coercion, of abduction, of fraud, of deception, of the abuse of power or of a position of vulnerability or of the giving or receiving of payments or benefits to achieve the consent of a person having control over another person, for the purpose of exploitation.Human trafficking does not take place in social and political isolation. The government is therefore tasked with the responsibility to ensure that this atrocity is nipped in the bud. When the social and political circumstances allow for and support the forceful theft of human labour, there is a need for deconstruction. A deconstruction of the laws that create this environment or an improvement of the same. Human trafficking is squarely located within the larger context of workers' rights, immigrant rights and human rights.According to the UNICEF Innocenti Insight, Kenya is a primary source of origin, transit and destination for human trafficking.This may be indicative of a general lack of concern by the government to deal with the atrocity. To this end, this research is hinged on mainly trying to figure out where the problems are in policy and regulation in order to improve Kenya’s status in the global arena as regards this subject.
Submitted in partial fulfillment of the requirements of the Bachelor of Laws Degree at Strathmore University Law School
Keywords: Human trafficking; Human Trafficking Legislation; Palermo Protocol; National Statutes